2010
DOI: 10.1080/17518251003730825
|View full text |Cite
|
Sign up to set email alerts
|

The effect of light intensity, film thickness, and monomer composition in styrene-based bioinspired polymers

Abstract: The effect of irradiation light intensity, film thickness, and polymer composition upon photo-irradiation of watersoluble polymers containing thymine was studied by ultraviolet (UV)-vis spectroscopy. Coatings of aqueous solution of the polymer on PET substrates were exposed to UV light at 254 nm through a standard mask. The effect of irradiation dose is similar to the typical behavior of photo-resists: the degree of crosslink increases over the time until it reaches saturation. The polymer composition effect s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…One can notice that a collapse has happened when comparing the two images illustrated in Figure 10. Li et al [38] have reported similar behavior for polycaprolactonetriolmalate. They have used this degradable biomaterial as a biological graft for bone scaffold formation.…”
Section: Dynamic Mechanical Thermal Analysissupporting
confidence: 49%
“…One can notice that a collapse has happened when comparing the two images illustrated in Figure 10. Li et al [38] have reported similar behavior for polycaprolactonetriolmalate. They have used this degradable biomaterial as a biological graft for bone scaffold formation.…”
Section: Dynamic Mechanical Thermal Analysissupporting
confidence: 49%
“…A baseline correction of the UV spectra with a fourth‐order polynomial function to correct the light scattering effect was applied. The decrease of the absorbance band at 270 nm together with the slight absorbance increase above 300 nm indicate the breakdown of the pyrimidine ring aromaticity by the loss of the C 5 =C 6 double bond of the thymine moiety in the VBT unit during the dimerization reaction ,. Contrary to the CPD that is fully transparent at λ >220 nm, the 6–4PP dimer contains the 5‐methyl‐2‐pyrimidone chromophore showing an absorption band with a maximum at 325 nm and a characteristic fluorescence emission between 340–480 nm .…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of the absorbance band at 270 nm together with the slight absorbance increase above 300 nm indicate the breakdown of the pyrimidine ring aromaticity by the loss of the C 5 =C 6 double bond of the thymine moiety in the VBT unit during the dimerization reaction. [18,32] Contrary to the CPD that is fully transparent at λ > 220 nm, the 6-4PP dimer contains the 5-methyl-2-pyrimidone chromophore showing an absorption band with a maximum at 325 nm and a characteristic fluorescence emission between 340-480 nm. [33] In fact, the simultaneous increment of the fluorescence excitation and emission spectra upon irradiation of the HCM (Figure 3A), indicates the formation of the fluorescent 6-4PP-like dimer by the degradation of the VBT unit in the (P 4 + /P 4À ) 3 shell.…”
Section: Uv-induced Dimerization Of the Vbt Copolymer In The Microcapmentioning
confidence: 99%
“…Due to the high level of intermolecular forces between each monomer, the VBT homopolymer is insoluble in water. Thus, VBT is often polymerized in different ratios with styrene derivative charged monomers, such as anionic vinyl phenyl sulfonate (VPS) salts [7] or cationic vinylbenzyl triethylammonium chloride (VBA) [8][9][10] which allows the copolymer to be soluble in water. Extending the knowledge achieved from the study of the natural phenomena related to thymine reactivity and intermolecular interactions has generated a diapason of potential applications [11][12][13][14] ranging from photoresist material [15,16] and organic-inorganic hybrid devices [2] to antibacterial coatings [17], drug delivery systems [3,[18][19][20], recyclable plastics [21], and biosensors [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ethyl alkyl arms on VBA can be replaced with alkyl groups of different chain lengths to vary the antimicrobial properties and applications [17]. To ensure that the presence of charged monomers would not interfere with the photo-cross-linking reaction of VBT moieties, irradiation studies have been performed on varying ratios of VBT-VBA copolymers to quantify the extent of their photodimerization and immobilization [8,10]. From such studies, it was found that linear VBT-VBA copolymer chains cross-link through adjacent thymine moieties to form an immobilized thin film.…”
Section: Introductionmentioning
confidence: 99%